Diagnosing the voids of knowledge in the transformation process in managing and standardizing smart city development: the case of the government of Indonesia - Panjaitan, Jenri M. P.; Bastian, Indra; Unggara, Ilham; Susanto, Efa Agus; Sumiyana, Sumiyana (Frontiers in Sustainable Cities, 2023)
Purpose This study investigates smart city development projects implemented by the Government of Indonesia (GoI) from 2017 at the regional and municipal levels. Moreover, it provides a critical perspective on the lack of knowledge of the transformation process, substantive knowledge, and the wide-regime-shifting balance of knowledge required to accomplish smart city development. From the project scope perspective, this research elaborates on technical defaults of the regional and municipal GoI's initiating, constructing, and implementing smart cities. Research methodology The authors conducted semi-structured interviews to explore how these project doers operate in each stage of the smart city development, including initiation, work in progress, implementation, and reporting. In addition, the research questions of this semi-structured interview are derived from this study's critical perspective and the knowledge domains of smart city development. Originality First, this study sheds light on the development of 100 smart cities by the GoI, with 50 financed but unfinished projects since 2017, indicating design failure. Second, we argue that the blueprint designed by the GoI smart communities does not demonstrate comprehensive political will or the conducting of socio-cultural and technical analyses to encourage and support the development of smart cities. Third, this study uniquely highlights that the GoI wants to build smart cities using collective cognition or mutual understanding, but lacks knowledge of the transformation process and substantive knowledge for system analysis and design, development, and implementation, leading to uncertainty and non-uniform approaches to smart city developments across various regions and municipalities. Fourth, this research criticizes the misalignment and imbalance of knowledge between the GoI, the targeted regions and municipalities, and all agents involved in developing smart cities. Findings The authors find four unique theme formulations: the GoI's behaviors in equivalencing with regular procurement, the voids of knowledge in the transformation process, substantive knowledge boundaries, and letting these projects progress without accompanying committed knowledge boundaries and working for a future without a signifier. Finally, this study suggests that the government should prioritize mastery of knowledge of the transformation processes in smart city development and implement agile strategies to ensure these projects' success and future benefits.